γδ T cells and cancer - Lukas Bolini; Seth B. Coffelt; Bruno Silva-Santos; David L. Wiest; Lorenzo Galluzzi (Journal of Clinical Investigation, 2026)
γδ T cells are a subset of lymphoid cells that, unlike their αβ lineage counterparts, express a heterodimeric TCR that mostly operates in an MHC-independent manner. γδ T cells are abundant in barrier tissues, where they continuously monitor epithelial cells for signs of stress or damage. Thus, γδ T cells are among the first responders to pathophysiological conditions, including viral infection and oncogenesis. Human γδ T cells can be classified based on TCR γ and δ chain usage into three main subsets: (a) Vγ9 + Vδ2 + cells, accounting for most circulating γδ T cells; (b) Vδ1 + cells, which are common in epithelial linings, and (c) Vδ3 + T cells, which are fairly rare but exhibit unique specificities. Moreover, both human and murine γδ T cells can assume a spectrum of states with divergent phenotypic and functional properties. Accumulating evidence demonstrates that γδ T cells can mediate robust anticancer effects or support tumor progression and resistance to therapy, depending on numerous variables, including functional state and tumor type. Here, we critically discuss the context-dependent interaction between γδ T cells and cancer, focusing on recent developments and the challenges facing current efforts to manipulate this versatile lymphocyte subset for therapeutic purposes.